The art of merchant banking: the Nigerian experience - Ebong, Ime Ekop (Nigeria: University of Lagos Press, 1993)
The author adopts a pragmatic approach to the business of merchant banking in Nigeria in simple and plain banking language. He emphasizing core activities, attributes and characteristics or merchant banking as compared to the activities of other financial institutions.
rua 05/09/16
Loans
Keywords: Merchant banks - Nigeria; Bank management - Nigeria; Merchant banks; Bank management; Nigeria